Formation and role of Neogene sediments from Tatra Mountains in the shaping of Czarna Orawa River alluvial plain - Krzaklewski, Paweł (Quaestiones Geographicae, 2012)
The paper presents researches that were conducted in Czarna Orawa River catchment, situated within the Tatra and Beskidy Mountains. Czarna Orawa River channel is segmental meandering system with the index of tortuosity up to 1.6. The aim of the article is to characterize gravels which were transported from the Tatra Mountains and their role in valley bottom formation. The gravels; originating from Beskidy and Tatra mountains, supply the alluvial cone of Czarny Dunajec. In Czarna Orawa Valley we meet coarser gravel (the Tatra Mountains gravel) and more angular than grains from the Beskidy Mountains. On the Holocene terraces in the valley gravel layer is 1-2 m thick. The grains are 1-6 cm in diameter and the biggest are found on the south bank (up to 20 cm). Between Jabłonka and Orawa Reservoir the change of petrographic composition is observed. Beneath Jabłonka village ﬂysh gravels are common, and in the lower part, in the neighbourhoods of Orawa Reservoir, more than 55% are granites and gneisses. Gravel se-diments are basic material building Holocene plain, showing fast erosional incision into the higher terrace level.